A highly generalized classifier for osteoporosis radiography based on multiscale fractal, lacunarity, and entropy distributions - Cui, Jingnan; Liu, Cheng Lei; Jennane, Rachid; Ai, Songtao; Dai, Kerong; Tsai, Tsung-Yuan (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Osteoporosis is a common degenerative disease with high incidence among aging populations. However, in regular radiographic diagnostics, asymptomatic osteoporosis is often overlooked and does not include tests for bone mineral density or bone trabecular condition. Therefore, we proposed a highly generalized classifier for osteoporosis radiography based on the multiscale fractal, lacunarity, and entropy distributions. Methods: We collected a total of 104 radiographs (92 for training and 12 for testing) of lumbar spine L4 and divided them into three groups (normal, osteopenia, and osteoporosis). In parallel, 174 radiographs (116 for training and 58 for testing) of calcaneus from health and osteoporotic fracture groups were collected. The texture feature data of all the radiographs were pulled out and analyzed. The Davies–Bouldin index was applied to optimize hyperparameters of feature counting. Neighborhood component analysis was performed to reduce feature dimension and increase generalization. A support vector machine classifier was trained with only the most effective six features for each binary classification scenario. The accuracy and sensitivity performance were estimated by calculating the area under the curve. Results: Interpretable feature trends of osteoporotic pathological changes were depicted. On the spine test dataset, the accuracy and sensitivity of binary classifiers were 0.851 (95% CI: 0.730–0.922), 0.813 (95% CI: 0.718–0.878), and 0.936 (95% CI: 0.826–1) for osteoporosis diagnosis; 0.721 (95% CI: 0.578–0.824), 0.675 (95% CI: 0.563–0.772), and 0.774 (95% CI: 0.635–0.878) for osteopenia diagnosis; and 0.935 (95% CI: 0.830–0.968), 0.928 (95% CI: 0.863–0.963), and 0.910 (95% CI: 0.746–1) for osteoporosis diagnosis from osteopenia. On the calcaneus test dataset, they were 0.767 (95% CI: 0.629–0.879), 0.672 (95% CI: 0.545–0.793), and 0.790 (95% CI: 0.621–0.923) for osteoporosis diagnosis. Conclusion: This method showed the capacity of resisting disturbance on lateral spine radiographs and high generalization on the calcaneus dataset. Pixel-wise texture features not only helped to understand osteoporosis on radiographs better but also shed new light on computer-aided osteopenia and osteoporosis diagnosis.